Natural Composition and Biosynthetic Pathways of Alkaloids in Medicinal Dendrobium Species - Song, Cheng; Ma, Jingbo; Li, Guohui; Pan, Haoyu; Zhu, Yanfang; Jin, Qing; Cai, Yongping; Han, Bangxing (Frontiers in Plant Science, 2022)
Dendrobium is the second biggest genus in the Orchidaceae family, some of which have both ornamental and therapeutic values. Alkaloids are a group of active chemicals found in Dendrobium plants. Dendrobine has emerged specific pharmacological and therapeutic properties. Although Dendrobium alkaloids have been isolated and identified since the 1930s, the composition of alkaloids and their biosynthesis pathways, including metabolic intermediates, alkaloid transporters, concrete genes involved in downstream pathways, and associated gene clusters, have remained unresolved scientific issues. This paper comprehensively reviews currently identified and tentative alkaloids from the aspect of biogenic pathways or metabolic genes uncovered based on the genome annotations. The biosynthesis pathways of each class of alkaloids are highlighted. Moreover, advances of the high-throughput sequencing technologies in the discovery of Dendrobium alkaloid pathways have been addressed. Applications of synthetic biology in large-scale production of alkaloids are also described. This would serve as the basis for further investigation into Dendrobium alkaloids.